Resolução de problemas : ações pedagógicas de professores de matemática dos anos finais do ensino fundamental - Santana, Geralda de Fatima Neri (2016)
In this research, we seek to answer the following question: which educational actions of teachers who teach Mathematics in Primary Education II can be identified when they work in the approach to problem solving in the teaching-learning process of Mathematics content? It is a qualitative research and was carried out with four teachers who teach Mathematics in public schools, and are linked to the Education Secretariat of the State of Paraná (SEED/PR), under the jurisdiction of the Regional Center of Maringa Education, State of Parana. We proposed the use of online questionnaire, interview and field diary as tools for data collection. a) The online questionnaire was sent to the email address (provided by the Maringa Regional Education Center) to mathematics teachers jurisdictional in that organ. Issues Questionnaire, among others, aimed to identify methodological trends are used by teachers in mathematics teaching content. b) the type of semi-structured interview sought to identify in this informal conversation, what the teacher actions in the classroom, in an educational with approach in the problem solving. c) the Field Diary to record the development of educational activities of teachers that indicated use problem solving. Such actions served as parameters to analyze the classes taught by teachers investigated and they refer to: a) propose the problem as a starting point, to introduce a new mathematics content that permits be solved by different strategies; b) discuss and cooperate in the interpretation and understanding of the statement and resolution strategies, giving voice to the students so that they can speak and/or demonstrate the ways used to solve the proposed problem; c) group students and allow time for the planning and execution of an elaborate plan; d) socialize with the class the strategies presented, promoting the development of concepts by students. The teachers participating in this research were named P6, P7, P9 and P11. Unfortunately, there was no time to observe the P6 classes; the delay in collecting these data was due to the strike of the classes in the state of Paraná in this year of 2015. After the analysis of the collected data, it was possible to identify that P6, P7, P9 and P11 showed both the verb form (Questionnaire) and oral (Interview) that work in problem-solving approach. As the Field Diary and in accordance with the theoretical framework we used, the surveyed teachers develop in classroom a theaching of mathematics from the perspective of problem solving. The P9 and P11 teachers use the problem as a starting point, enable active student participation in the discussion of solving strategies favoring the construction of concepts. Such pedagogical actions indicate a teaching by way of problem solving. The teaching approach of the P7 teacher matches the resolution of problems such as application of knowledge, because their actions are initiated from the concepts, problems come later as application of knowledge. Therefore it would be teach to the problem solving.